CONVERGENCE PROGRAMMES AS AN ECONOMIC POLICY TOOL WITHIN THE EUROPEAN UNION - Postuła, Marta; Sobolewska, Justyna; Tomkiewicz, Jacek (Acta Scientiarum Polonorum. Oeconomia, 2018)
The article presents the results of research indicating to what extent the convergence programmes submitted to the European Commission prove country’s willingness to improve the fiscal policy in a desired way and to what extent they constitute a mere fulfilment of a formal duty without any actual intent to achieve the indicated macroeconomic parameters. The conducted analyses allow to conclude that the European countries, while preparing the prognostic documents, have a tendency to hide the scale of the fiscal imbalance that reflects a lack of consistency between the current balance of the sector and an increase in the public debt. The results of quantitative and qualitative research indicate that, regardless of the implemented regulatory solutions at the EU level in the framework of the modified Stability and Growth Pact, certain flaws of the tools used for economic policy coordination at the European level are still visible.